Sustainably Sourced Mesoporous Carbon Molecular Sieves as Immobilization Matrices for Enzymatic Biofuel Cell Applications - Torrigino, Federica; Nagel, Marcel; Peng, Zhujun; Hartmann, Martin; Herkendell, Katharina (Catalysts, 2023)
Ordered mesoporous carbon CMK-3 sieves with a hexagonal structure and uniform pore size have recently emerged as promising materials for applications as adsorbents and electrodes. In this study, using sucrose as the sustainable carbon source and SBA-15 as a template, CMK-3 sieves are synthesized to form bioelectrocatalytic immobilization matrices for enzymatic biofuel cell (EFC) electrodes. Their electrochemical performance, capacitive features, and the stability of enzyme immobilization are analyzed and compared to commercially available multi-walled carbon nanotubes (MWCNT) using cyclic voltammetry and electrochemical impedance spectroscopy (EIS). The anodic reaction in the presence of glucose oxidase (GOx) and ferrocene methanol (FcMeOH) on the sustainably sourced CMK-3-based electrodes produces bioelectrocatalytic current responses at 0.5 V vs. saturated calomel electrode (SCE) that are twice as high as on the MWCNT-based electrodes under saturated glucose conditions. For the cathodic reaction, the MWCNT-based cathode performs marginally better than the CMK-3-based electrodes in the presence of bilirubin oxidase (BOD) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS2−). The CMK-3-based EFCs assembled from the GOx anode and BOD cathode results in a power output of 93 μW cm−2. In contrast, the output power of MWCNT-based EFCs is approximately 53 μW cm−2. The efficiency of CMK-3 as a support material for biofuel cell applications is effectively demonstrated.
CRIS-Team Scopus Importer:2024-12-16
Keywords: bilirubin oxidase; CMK-3; cyclic voltammetry (CV); electrochemical impedance spectroscopy (EIS); enzymatic biofuel cells (EFCs); glucose oxidase; immobilization; mesoporous carbon; MWCNT; sustainable carbon